DIFFERENT PERCEPTION ON TENNIS LEARNING METHODOLOGY - BUCĂTARU R.M; MOISESCU P.C (Editura Universitatii Transilvania din Brasov, 2019)
Tennis has become a sport increasingly known and loved by children but less effective to continue their sports activities. There are numerous reasons why practitioners leave tennis at an early age. In classical tennis , the learning process is spread over several years, being a long-term activity(6-8years). Tennis 10 is a program that was created and implemented by the International Tennis Federation (ITF) in the early 2000s as part of a campaign carrying the title "Tennis Play and Stay" .Tennis Play and Stay campaign aims to promote tennis as a game easy to practice, purpose and fun to maintain health and to ensure that all novice players can still serve and hit the ball at the first lesson. With this work I wanted to compare the two learning methodologies.